Antitumour and immunosuppressive activity of hydroxyanthraquinones and their glucosides - Hilgert, I; Cudlín, J; Steinerová, N; Vanĕk, Z (Folia biologica, 1977)
Both isomeric monohydroxyanthraquinones (1a, b), three dihydroxyanthraquinones (alizarin 1c, chrysazin 1d, and anthraflavin 1e) and corresponding acetylated (2) and free (3) beta-D-glucosides were screened for antitumour and immunosuppressive activity. Furthermore, four O-acetyl and O-benzyl derivatives of alizarin (5a--d) were tested. Antitumour activity was judged by the inhibition of growth of syngeneic tumours in the treated recipients and immunosuppressive activity by the effect on tumour growth or on skin graft survival in pretreated allogeneic recipients; as standard of reference served the activity of certain cancerostatic or immunosuppressive drugs used in clinical practice. 1-Hydroxyanthraquinone (1a), alizarin (1c), chrysazin (1d), acetylated glucoside of 2-hydroxyanthraquinone (2b), 2-benzylalizarin (5c), and 1-acetyl-2-benzylalizarin (5d) were found to exhibit antitumour activity. Distinct immunosuppressive activity was detected in alizarin (1c), acetylated glucoside of 1-hydroxyanthraquinone (2a), acetylated glucoside of 2-hydroxyanthraquinone (2b), acetylated glucoside of chrysazin (2d), 2-acetylalizarin (5a), and 1-acetyl-2-benzylalizarin (5d). The group of hydroxyanthraquinone glucodises (3a--3d) exhibited neither antitumour nor immunosuppressive activity.
Keywords: Mice; glukosidy; Glucosides; glykosidy; Immunosuppressive Agents; přežívání štěpu; Animals; Anthraquinones; experimentální nádory; Graft Survival; anthrachinony; Glycosides; zvířata; Mice, Inbred C57BL; myši; Neoplasms, Experimental; myši inbrední C57BL; imunosupresiva